Preparation and properties of polybenzoxazole-based gas separation membranes: A comparative study between thermal rearrangement (TR) of poly(hydroxyimide) and thermal cyclodehydration of poly(hydroxyamide). (5th November 2015) - Kushwaha, Ashish; Dose, Michelle E.; Smith, Zachary P.; Luo, Shuangjiang; Freeman, Benny D.; Guo, Ruilan
Abstract: This comparative study focuses on the cyclodehydration reaction of poly(hydroxyamide)s (PHAs) and the thermal rearrangement (TR) reaction of aromatic poly(hydroxyimide)s (APIs) to produce polybenzoxazoles (PBOs) for application as gas separation membranes. Systematic comparisons between the two routes showed that PHA cyclodehydration can produce fully converted PBO membranes at a temperature more than 100 °C lower than the API-TR route. Gas separation performance of PHA–PBOs is comparable to API-TR polymers, and PHA–PBOs are considerably more mechanically robust. More importantly, PBO films can be produced equally well in both air and inert atmospheres via the PHA cyclodehydration route. The PHA–PBOs formed in air have statistically the same physical and transport properties as those formed in N2 . The present study provides fundamental information regarding the PHA-to-PBO cyclodehydration process. Graphical abstract: Highlights: Robust PBO membranes were prepared via solid-state PHA cyclodehydration. PHA–PBO films showed high permeability and selectivity comparable to TR membranes. PHA-to-PBO cyclodehydration temperature is 100 °C lower than in TR process. The same PBO films can be obtained under both air and N2 atmosphere from PHA route.